Enhanced Charge Carrier Mobility in Two‐Dimensional High Dielectric Molybdenum Oxide (Adv. Mater. 1/2013). (2nd January 2013) - Balendhran, Sivacarendran; Deng, Junkai; Ou, Jian Zhen; Walia, Sumeet; Scott, James; Tang, Jianshi; Wang, Kang L.; Field, Matthew R.; Russo, Salvy; Zhuiykov, Serge; Strano, Michael S.; Medhekar, Nikhil; et al.
<x xml:space="preserve">Abstract</x> Extremely high carrier mobilities are achieved in layered molybdenum oxide by Sivacarendran Balendhran, Kourosh Kalantar‐zadeh, and co‐workers on page 109. This is achieved by intercalation of the octahedral molybdenum oxide lattice with hydrogen, which tunes the bandgap of the material. Carrier mobilities of 1100 cm2 V−1 s−1 and greater are attained, highlighting the potential of ultrathin molybdenum oxide for high speed nanoelectronics. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>